Meningkatkan Pemahaman Konsep Peserta Didik Pada Materi Persamaan dan Pertidaksamaan Linear Satu Variabel Dengan Model Problem Solving Dikelas VII MTs Al Khairat Kec. Ibu Tengah - Asmira Sudiman; Jufri Ade; Bambang Sudin; Yani Awal; Nurlaila H. Tasanif; Rusdyi Habsyi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this research is to increase students' understanding of the concept of a one-variable linear equation system with a problem solving approach in Class VII MTs Al-Khairat Kec. Middle Mother. The method used in this research is Classroom Action Research (CAR). While the technique in data collection is data obtained from sources of students and teachers in conducting qualitative and quantitative analysis. The results of data analysis prove that the comparison of the average value of student learning outcomes after applying learning using the Problem Solbing model has an increase in learning outcomes as much as 16.33%, from 65.89% it increases to 82.22%. And an increase of 4.26%, namely from the first cycle of 82.22% to 86.48%. This success can be said because of the comparison from pre-cycle to cycle I (good qualification level) and from cycle I to cycle II (excellent qualification level). Therefore, the research can conclude that 1) Efforts to improve students' understanding of concepts in the one variable equation system material with a problem solving approach in class VII MTs Al-Khairat Kec. Mother is being applied effectively and efficiently, smoothly and completely, which can be seen from the seriousness of the students in listening to the lesson. The results of the observation show that students are not very happy but still need a long time to adjust to the learning environment. 2) The problem solving method can improve students' conceptual understanding skills on the one-variable linear equation system material at MTs Al-Khairat Kec. Ibu Tengah, this can be seen in the learning outcomes that the average value of the results of learning outcomes for a single variable linear equation system using the prosolving method has increased by 16.33%, from 65.89% to 82.22%. And an increase of 4.26%, namely from the first cycle of 82.22% to 86.48%. This success can be said because of the comparison from pre-cycle to cycle I (good qualification level) and from cycle I to cycle II (excellent qualification level).